Symptomatic Extra-Adrenal Myelolipoma in the Spleen - Jonathan A. Nitz; Jeremy Huckleby; Elise H. Hwang; Melissa G. Medina; Samuel J. Pera; Sonia T. Orcutt (Case Reports in Surgery)
A 42-year-old male patient presented with intermittent abdominal pain and gastrointestinal discomfort present for 4 years. Work-up included ultrasound and computed tomography, which identified a fat-containing splenic mass 5.6 cm in size. Due to recurrent symptoms, the patient sought medical care again. Subsequent images showed an increase in size to 7.6 cm, which was concerning for neoplasm. This was removed via open splenectomy, which was challenging due to intra-abdominal adhesions despite never having had any abdominal surgery. The patient’s recovery was uncomplicated. Pathologic assessment indicated that the mass was a myelolipoma. Extra-adrenal myelolipomas are rare and typically found within the retroperitoneum but are extremely rare within the spleen. This case report adds the 6th such case to the literature and demonstrates the need for it to remain in the differential diagnosis of patients with fatty splenic masses, as well as that splenectomy is an appropriate treatment.